Faktor Kritis Kesiapan E-Learning Pendorong Perfoma Belajar Ekonomi Siswa SMA Selama Pandemi Covid-19 - Yohana Paramita; Waspodo Tjipto Subroto (Universitas Pendidikan Mandalika (UNDIKMA), 2021)
This study aims to analyze the effect of e-learning readiness factors, including self-competency, perceived usefulness, self-directed learning, motivation, and financial on the economic learning performance of high school students. This study used a quantitative approach. A total of 177 students were involved in this study. The data were collected through questionnaires and documentation. Regression analysis was used to analyze the data. The results of the study showed that four factors of e-learning readiness, namely self-competency, perceived usefulness, self-directed learning, and financial partially had a significant effect on students' economic learning performance (exam scores). Self-directed learning emerged as the strongest factor for driving students' economic learning performance (exam scores), and sequentially followed by self-competency, financial, and perceived usefulness factors. Another factor, namely motivation partially has no effect on students' economic learning performance (assign-ment and exam scores). Meanwhile, simultaneously all e-learning readiness factors have an effect on students' economic learning performance (assignment and exam scores).